2016
DOI: 10.1016/j.jtho.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Subpopulations at High Risk for Lung Cancer

Abstract: Introduction Two thirds of newly diagnosed lung cancer patients in the U.S. would not meet the current USPSTF (United States Preventive Services Task Force) screening criteria, suggesting a need for amendment to the high-risk definition. To provide evidence of additional high-risk subpopulations and estimated gains and losses, we conducted a two-step study using three cohorts. Methods Two prospective cohorts are comprised of 5988 primary lung cancer patients diagnosed between 1997-2011 (Hospital) and 850 def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
(39 reference statements)
1
30
0
Order By: Relevance
“…Lung cancer screening with low‐dose computed tomography targeting high‐risk ever‐smokers has been widely adopted in the United States based on a 20% reduction in mortality from lung cancer among high‐risk individuals using National Lung Screening Trial inclusion criteria, which comprise age and smoking history . However, approximately two‐thirds of newly diagnosed lung cancer patients reportedly fail to meet the U.S. Preventive Services Task Force high‐risk criteria . Moreover, epidemiological studies have reported that an estimated 10–25% of lung cancers occur in never‐smokers, and the proportion of lung cancer in never‐smokers has been increasing over time .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer screening with low‐dose computed tomography targeting high‐risk ever‐smokers has been widely adopted in the United States based on a 20% reduction in mortality from lung cancer among high‐risk individuals using National Lung Screening Trial inclusion criteria, which comprise age and smoking history . However, approximately two‐thirds of newly diagnosed lung cancer patients reportedly fail to meet the U.S. Preventive Services Task Force high‐risk criteria . Moreover, epidemiological studies have reported that an estimated 10–25% of lung cancers occur in never‐smokers, and the proportion of lung cancer in never‐smokers has been increasing over time .…”
Section: Introductionmentioning
confidence: 99%
“…3 However, approximately two-thirds of newly diagnosed lung cancer patients reportedly fail to meet the U.S. Preventive Services Task Force high-risk criteria. 4 Moreover, epidemiological studies have reported that an estimated 10-25% of lung cancers occur in never-smokers, and the proportion of lung cancer in never-smokers has been increasing over time. 5,6 This highlights a need to identify additional subpopulations at increased risk for lung cancer among low-risk populations and never-smokers while considering factors other than smoking and aging.…”
mentioning
confidence: 99%
“…For a long time, adverse symptoms of chronic poisoning in heavy smokers had not been apparent. Scientific research focused especially on cardiology and oncology has demonstrated a strong connection between smoking and disease incidence of the cardiovascular system and cancer [4][5][6][7]. The World Health Organization (WHO), in collaboration with governmental and nongovernmental organizations, have taken many steps for countering the tobacco epidemic.…”
mentioning
confidence: 99%
“…The primary group that this adds comprises those who smoked 30 pack-years but have quit 15 or more years ago and remain at high risk for lung cancer. In a retrospective cohort of patients who were diagnosed with lung cancer, Yang et al suggest that expanding the criteria of screening to include those who quit smoking 15–30 years ago would have the potential to include 16% more of those who got cancer with acceptable cost and minimal harm 36 .…”
Section: Screening For Lung Cancer: the Story So Farmentioning
confidence: 99%